Examination Timetabling Using Genetic Algorithm Case Study : KUiTTHO - Mohd. Zaki, Mohd. Salikon (2005)
Genetic Algorithm (GA) is one of the most popular optimization solutions. It has been implemented in various applications such as scheduling. The flows of GA are using selection, crossover and mutation operators applied to populations of chromosomes. This paper reports the powerful techniques using GA in scheduling. Examination timetabling problem is one of the applications in scheduling. In one aspect, it deals with students such that it fulfils the process time slot. These aspects are important for the examination can be done in a smooth way and no students can sit more than one exam in a same time slot. The other constraint is the student workload should be arranged less than three exams in a row. The examination timetabling problem at Kolej Universiti Teknologi Tun Hussein Onn (KUiTTHO) is introduced and the prototype has been developed using Java language. The prototype suggested several feasible solutions to the user.